Traditional knowledge and practice of the Triassic variegated clay from Silesia (Krasiejów), Poland, in human medicine - Izabela Spielvogel; Krzysztof Spałek; Krzysztof Badora; Jarosław Proćków (BMC, 2021)
Abstract Background Krasiejów clay (in German: Krascheow) became famous following the discovery of numerous fossilised bones of Upper Triassic amphibians and reptiles, which have been extracted from clay deposits since the 1980s. These organic remnants remained in Krasiejów clay due to the large amount of slime deposits and the optimal concentration of basal mineral salts. The main aims of the paper are to determine the historical evolution of the use of clay in Silesia for therapeutic purposes and to provide a summary of the historical uses of Krasiejów clay as a medical treatment, based on the knowledge of the local population. Methods The mode of utilisation of Triassic variegated claystone treatment from Krasiejów was surveyed based on oral communication with local people. This information was collected over the last 35 years (1982-2017) by interviewing those who used clay as a traditional remedy, especially the eldest residents. Each resident was interviewed several times regarding the healing properties of Krasiejów clay, including the causes and symptoms of the ailments treated, mode of clay preparation, application methods, and dosage through semistructured interviews. Results Clay from Krasiejów was used in medicine after proper preparation. The clay underwent a complicated preparation process before the use in wraps, compresses, poultices, and baths as a skin peeling agent and even as a potion to be drunk. All recorded applications, diseases, and ailments to which it were applied are described here in detail, divided into treatments with warm, and cold clay. Conclusions Krasiejów variegated claystone had different benefits depending on the form in which it was used; different diseases were treated with warm and cold clay. According to informants, many of these diseases have been successfully treated, in particular eczema of various origins, purulent ulcers on the skin, and following internal use, digestive ailments. According to informants, in cases where the disease could not be cured, for instance, psoriasis, a significant improvement in the condition of the skin was visible in a short period of time. Clay from Krasiejów should be subjected to more detailed physicochemical analyses to determine its exact chemical composition and healing properties.